The optimum mooring configuration with minimum sensitivity to remove a mooring line for a semi-submersible platform. (September 2021) - Tabeshpour, Mohammad Reza; Seyed Abbasian, S. Mohammad Reza
Abstract: Mooring lines may be damaged under severe conditions during the life of an offshore platform. In the event of a mooring failure, it is possible to break remaining mooring lines in a severe condition, which ultimately leads to the total structural failure; Therefore, the post-failure analysis is very important for the mooring system. In this study, the Amir-Kabir semi-submersible platform has been modeled which is installed in 700 m' depth of the Caspian Sea, and random waves have been generated towards the structure in the form of the JONSWAP wave spectrum according to the conditions of the Caspian Sea. For analysis, four different mooring configurations have been considered. Then, in each analysis, one of the four mooring lines has been broken during the storm, and the effect of the failure has been analyzed on the platform responses. In other words, the responses of the six degrees of freedom have been compared with each other derived from the analysis. Finally, the optimum mooring configuration has been chosen to reduce structure motions after the mooring failure.